VDR Polymorphisms in Autoimmune Connective Tissue Diseases: Focus on Italian Population - Andrea Latini; Giada De Benedittis; Carlo Perricone; Serena Colafrancesco; Paola Conigliaro; Fulvia Ceccarelli; Maria Sole Chimenti; Lucia Novelli; Roberta Priori; Fabrizio Conti; Cinzia Ciccacci; Paola Borgiani (Journal of Immunology Research)
Vitamin D is an important hormone involved in various physiologic processes, and its activity is linked to binding with vitamin D receptor (VDR). Genetic polymorphisms in the VDR gene could modulate the expression or function of the receptor and, consequently, alter the effects of vitamin D. Variants in VDR gene have been associated with susceptibility to many illnesses sensitive to vitamin D administration and to autoimmune disorders, but no data are available regarding autoimmune connective tissue diseases in Italian population. We analyzed three VDR polymorphisms in 695 Italian patients with autoimmune connective tissue diseases (308 with systemic lupus erythematosus (SLE), 195 with primary Sjogren’s syndrome (pSS), and 192 with rheumatoid arthritis (RA)) and in 246 healthy controls with the aim to evaluate a possible association of VDR SNPs with susceptibility to these diseases in the Italian population. Genotyping of rs2228570, rs7975232, and rs731236 in VDR gene was performed by an allelic discrimination assay. A case/control association study and a genotype/phenotype correlation analysis have been performed. We observed a higher risk to develop SLE for rs2228570 TT genotype (P=0.029, OR=1.79). No association was observed between susceptibility to pSS or RA and this SNP, although this variant is significantly less present in RA patients producing autoantibodies. For rs7975232 SNP, we observed a significant association of the variant homozygous genotype with SLE (P=0.009, OR=1.82), pSS (P=0.046, OR=1.66), and RA (P=0.028, OR=1.75) susceptibility. Moreover, we reported associations of this genotype with clinical phenotypes of SLE and pSS. Lastly, the GG genotype of rs731236 was associated with a lower RA susceptibility (P=0.045, OR=0.55). Our results show that the explored VDR polymorphisms are significantly associated with autoimmune connective tissue disorders and support the hypothesis that the genetic variability of VDR gene may be involved in susceptibility to these diseases in Italian population.